Agentes etiológicos de Faringotonsilites agudas em pacientes adultos de São Carlos - Grandin Filho, Pedro Gimenes (Universidade Federal de São Carlos, 2023)
Introduction: Pharyngitis is a very common infection of the therapeutic tract and can be caused by bacteria, viruses and fungi. The etiological agents involved in the etiology of acute pharyngotonsillitis in our environment are unknown. Objective: This project aimed to investigate the etiology of acute pharyngotonsillitis as part of a research project on the use of photodynamic therapy in the treatment of acute pharyngotonsillitis. Patients and methods: Patients over 18 years of age with acute sore throat confirmed by clinical assessment were included in the photodynamic therapy study if they signed an informed consent form. The etiological investigation of the protocol included collection of oropharyngeal swab for rapid test for Group A beta-hemolytic Streptococcus; Gram stains and general culture on blood, chocolate, and Mac Conkey agar; polymerase chain reaction (PCR) for Fusobacterium necrophorum and detection panel of virus detection by polymerase chain reaction (influenza A and B virus, adenovirus, rhinovirus, OC43 coronavirus, Epstein-Barr virus, herpes simplex virus, and coronavirus -19). Preliminary results: From May 20, 2019 to January 29, 2020, 47 patients with acute pharyngotonsillitis were included in the study, 53.2% male, with a mean age of 23.6 years. The etiology was bacterial in 20 patients (42.6%), viral in seven patients (14.9%), and mixed – bacterial and viral in 5 patients (10.6%). GAS was responsible for 25.5% of cases, Fusobacterium necrophorum for 10.6%, and GBS for 4.3% and Staphylococcus aureus for 4.3%. Regarding viruses, HSV was responsible for 8% of cases, and EBV for 4.3%. All isolates of Group A beta-hemolytic Streptococcus were sensitive to penicillin, between 55 and 60% were resistant to macrolides and 50% were resistant to clindamycin.
Etiological agents of acute Pharyngotonsillitis in adult patients in São Carlos
Keywords: Faringite; SARS-CoV-2; Terapia Fotodinâmica; Pharyngotonsillitis; Photodynamic Therapy; CIENCIAS DA SAUDE::SAUDE COLETIVA::EPIDEMIOLOGIA